Perspectives on Creating Clinically Relevant Blast Models for Mild Traumatic Brain Injury and Post Traumatic Stress Disorder Symptoms - Brenner, Lisa; Bahraini, Nazanin; Hernández, Theresa D. (Frontiers in Neurology, 2012)
Military personnel are returning from Iraq and Afghanistan and reporting non-specific physical (somatic), behavioral, psychological, and cognitive symptoms. Many of these symptoms are frequently associated with mild traumatic brain injury (mTBI) and/or post traumatic stress disorder (PTSD). Despite significant attention and advances in assessment and intervention for these two conditions, challenges persist. To address this, clinically relevant blast models are essential in the full characterization of this type of injury, as well as in the testing and identification of potential treatment strategies. In this publication, existing diagnostic challenges and current treatment practices for mTBI and/or PTSD will be summarized, along with suggestions regarding how what has been learned from existing models of PTSD and traditional mechanism (e.g., non-blast) TBI can be used to facilitate the development of clinically relevant blast models.